EFFICACY OF ALPHA-ADRENERGIC RECEPTOR ANTAGONISTS IN THE TREATMENT OF DISTAL URETERIC STONES: A PAEDIATRIC STUDY - Brohi, Illahi Bux; Bhatti, Muhammad Shahid; Siyal, Roshan Ali; Ali, Farhan; Kaimkhani, Zulfiqar; Laghari, Hamid Raza (Journal of Ayub Medical College Abbottabad, 2022)
Background: European association of urology (EAU) recommended Î±- blockers for managing distal ureteric stones in the paediatric population. This paper will help to understand the efficacy of Silodosin as a medical expulsive agent for distal ureteric stones in children, along with the required time duration of stone expulsion. Methods: Forty participants were enrolled and evaluated for complaints, pain severity, associated symptoms, and ultrasound was done to confirm the position and size of the distal stone. Follow-ups were scheduled after every 7 days (1 week) for redo ultrasound and assessment of the stone position. Data was entered and analyzed in the SPSS version 23. To evaluate the significance of data chi-square test was performed, p-value <0.005 was considered significant. Results: The minimum and maximum age limits recorded are 3 years and 18 years respectively with a mean age of 9.5±4.5 years and mean stone size was measured as 0.6±0.1 cm. Distribution of stone size indicated the minimum size of 0.4 cm and maximum of 1.0 cm stone in study subjects. Maximum stone expulsion was reported within 14 days or an initial 2 follow-up scans. Conclusion: The efficacy of Silodosin and medical expulsive therapy evaluated the effect on pain management as pain episodes declined with Silodosin treatment and spontaneous passage of stones were increased within the first 14 days of treatment. This study will be a beneficial contribution in literature especially in a developing country population where paediatric urolithiasis is on expansion and ongoing